Star trek classics (2011), volume 3 ebook Encounters with the unknown. - Abnett, Dan (Star Trek Classics (2011), 2012)
Lost in the Delta Quadrant, Captain Janeway and the crew of the U.S.S. Voyager NCC-74656 have been seeking a way home for years. But their quest is interrupted by encounters with an astonishing variety of foes - and a few new friends. This collection contains four tales that exemplify all that''s best about the adventures of Voyager: "False Colors", "Avalon Rising", Elite Force", and "Planet Killer". Author: Nathan Archer, Janine Ellen Young, Doselle Young, Dan Abnett, Andy Lanning, Kristine Kathryn Rusch, Dean Wesley Smith. Illustrator: Jeffrey Moy, David Roach, Robert Teranishi, Drew Struzan. © 2012 Paramount Pictures Corporation. © CBS Studios Inc.